Chinese foreign direct investment in Latin America and the Caribbean : China-Latin America cross-council taskforce - Chen, Taotao (ECLAC SantiagoCL, 2013)
Proposes that more attention should be paid to the strategies and practices of Chinese companies in Latin America and to the features that set them apart from others.